Experience Group Insights of Obese Adults Aged 35-50 with Knee Osteoarthritis - George E. Sayegh BS; Scott Wallace JD, MBA; Karl Koenig MD, MS; Elizabeth Teisberg PhD; David Ring MD, PhD (Journal of Patient Experience)
Fifteen patients between 35 and 50 years of age, with a body mass index (BMI) over 35 with knee osteoarthritis participated in small group, facilitator-guided, interactive discussions (experience groups). Using initial inductive coding followed by deductive classification, 2 coders identified themes related to outcomes including difficulty engaging in meaningful work and social isolation in the capability realm, feelings of depression in the comfort realm, and desiring small achievable goals and consistent support in the calm realm. Themes regarding gaps in care included lack of roadmap and inadequate support. The obstacles to health were debilitating pain, despair due to isolation and stigmatization, hopelessness regarding treatment, perceived lack of clinician empathy and distrust, and frustration with the association of knee osteoarthritis with aging. Effective musculoskeletal specialty care can anticipate these patient needs, particularly for circumstances where nonoperative, accommodative health strategies are favored.